Nick and Tesla's secret agent gadget battle : a mystery with spy cameras, code wheels, and other gadgets you can build yourself - Pflugfelder, Bob, 1967-; Hockensmith, Steve (Quirk Books, 2014)
"After foiling a gang of kidnappers and fending off an army of robots, 11-year-old siblings Nick and Tesla Holt could use a little rest! But as their third mystery opens, they discover there's a spy in their midst, searching for secrets in the home of their beloved (and slightly crazy) Uncle Newt. Is it the new laboratory assistant? The exterminator? The housekeepers? Or someone completely unexpected? To expose the mystery agent, Nick and Tesla must engineer all kinds of outrageous contraptions, from code wheels and fingerprint powder to spy cameras and burglar detectors. Best of all, instructions are included throughout the story, so you can build the projects, too!" --Page 4 of cover.